The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/s21144624
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of a SiO2 Shell of Variable Thickness and Chemical Composition to Carbonyl Iron: Synthesis and Microwave Measurements

Abstract: Protective SiO2 coating deposited to iron microparticles is highly demanded both for the chemical and magnetic performance of the latter. Hydrolysis of tetraethoxysilane is the crucial method for SiO2 deposition from a solution. The capabilities of this technique have not been thoroughly studied yet. Here, two factors were tested to affect the chemical composition and the thickness of the SiO2 shell. It was found that an increase in the hydrolysis reaction time thickened the SiO2 shell from 100 to 200 nm. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…They can be expressed separately by the formula ε r = ε − jε" and µ r = µ − jµ". (ε is the real part of permittivity, ε" is the imaginary part of permittivity, µ is the real part of permeability, and µ" is the imaginary part of permeability) [28][29][30]. As shown in Figure 4a-c, the ε values of the SiO 2 @Fe 3 C/Fe@NCNT-GT varied in a range of 16.63−9.81, and the ε" values of the SiO 2 @Fe 3 C/Fe@NCNT-GT varied in a range of 6.15−2.44.…”
Section: Resultsmentioning
confidence: 99%
“…They can be expressed separately by the formula ε r = ε − jε" and µ r = µ − jµ". (ε is the real part of permittivity, ε" is the imaginary part of permittivity, µ is the real part of permeability, and µ" is the imaginary part of permeability) [28][29][30]. As shown in Figure 4a-c, the ε values of the SiO 2 @Fe 3 C/Fe@NCNT-GT varied in a range of 16.63−9.81, and the ε" values of the SiO 2 @Fe 3 C/Fe@NCNT-GT varied in a range of 6.15−2.44.…”
Section: Resultsmentioning
confidence: 99%
“…Since the maximum thickness of the shell is limited to 200 nm [ 42 ] in the one-stage Stöber synthesis, a multi-iterative deposition technique was studied. One “iteration” here was the full cycle of deposition including TEOS hydrolysis and air drying.…”
Section: Methodsmentioning
confidence: 99%
“…The filler volume in all cases was estimated as 20 vol.%. The samples were formed in the toroidal shape and placed inside a standard 7/3 mm coaxial transmission line [ 42 ]. S-parameters of the composite samples placed in the airline were measured in the frequency range of 0.1 to 20 GHz with a vector network analyzer (VNA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With its good stability and antioxidation features, SiO 2 has been frequently used in core-shell or yolk-shell structured microwave absorbing materials. [29][30][31][43][44][45][46][47][48] Meanwhile, several research studies have shown that the low permittivity of SiO 2 can reduce the complex permittivity of the composites and thus appropriate impedance matching can be achieved, which allows incident microwaves to enter the absorber as much as possible, and greatly improves the microwave absorption properties of the samples. [43][44][45][46][47][48][49][50][51] For example, Fan et al synthesized RGO-supported core-shell SiO 2 @SiO 2 /carbon hybrid microspheres and their minimum RL was found to be À24.1 dB with a thickness of 2.8 mm and a loading ratio 30 wt%.…”
Section: Introductionmentioning
confidence: 99%